The Influence of Project-based Learning Integrated STEAM on the Creative Thinking Skills - Adelia Dwinta Pramashela; Hadi Suwono; Sulisetijono Sulisetijono; Ucik Agusti Wulanningsih (BIOEDUKASI, 2023)
Project-based learning can develop the student’s creative thinking skills because students will learn better if they are engaged in a meaningful learning activity. The implementation of this learning strategy with a STEAM approach supported the students to create a product. This study was aimed to measure to investigating the effect of project-based learning integrated STEAM on creative thinking skills of class X students of SMA 6 Malang. The method used in this study was quasi-experimental research using Pretest Posttest Nonequivalent Control Group Design. The result of an essay test was analyzed by using analysis of covariance (ANCOVA) test followed by post hoc LSD test. The research result showed that the implementation of PBL-STEAM had a significant effect on the student’s creative thinking skills. Moreover, the post hoc LSD test findings showed several variations between the PBL strategy and the conventional learning strategy in the notation. These findings suggested that the project-based learning strategy might develop students' capacity for creative thinking skills.